NILAI SPIRITUAL DAN SOSIAL DALAM AL-‎QUR’AN SURAH MARYAM AYAT 12-14‎ PADA PENDIDIKAN ANAK - Nurul Irvianti; Hunainah Hunainah (Program Studi Pendidikan Agama Islam Program Pascasarjana Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2019)
The aim of this research is to analyze the implementation of spiritual and social values ​​in the Qur'an sura verse 12-14 on children's education at SD IT Iqra Serang. Includes implementation, obstacles and efforts to overcome them. The research method used is comparative qualitative descriptive. Data sources came from interviews with school principals, Islamic Religious Education teachers, homeroom grades 1 through third and students from first to third grade. In addition, the data were also obtained from observations and documentation studies. The data analysis process in this study uses the Spradley model which consists of data reduction, data presentation, conclusion and verification. As for the validity of the data using data triangulation techniques. Based on the analysis of the field result data, it was found that the implementation of spiritual and social values ​​in the Qur'an sura verse 12-14 on children's education at SD IT Iqra Serang City. The results of the analysis and research show that: there are eight spiritual values ​​and social values ​​in the Qur'an Surah Maryam verses 12-14, namely: (1) truly, (2) wisdom, (3) mercy, (4) purity , (5) taqwa, (6) devoted to both parents, (7) not arrogant, (8) not disobedient, the implementation of spiritual values ​​and social values ​​in SD IT Iqra Serang City with customs like (1) muroja 'ah, (2) Reciting Al-Qur'an, (3) memorize verses of the Qur'an, (4) duha prayer and dhuhur prayer in congregation, (5) recitation of du'a before and after the lesson, (6) social service activities, and (7) activities learn how to teach.